2013
DOI: 10.14742/ajet.282
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the TPACK of Taiwanese secondary school science teachers using a new contextualized TPACK model

Abstract: Technological pedagogical and content knowledge (TPACK) has been one of the steering theoretical concepts widely employed by researchers in order to examine and develop teachers' knowledge of integrating technology into teaching. Existing research on TPACK shows little about in-service secondary school science teachers' TPACK through a quantitative approach. The purposes of this study were to explore TPACK of secondary school science teachers using a new contextualized TPACK model. Associations between in-serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 43 publications
9
68
2
9
Order By: Relevance
“…Results of the study by Jang and Tsai [59] showed that a teacher's TPACK is directly related to the amount of their teaching experience. Teaching experience and gender were also confirmed to be the factors affecting the TPACK among Science teachers from secondary schools by the following study [60]. The ways teachers think of and use technology to improve teaching Science may be significantly affected also by the structure and content of a given subject [49].…”
Section: Theoretical Framework (Tpack)mentioning
confidence: 62%
“…Results of the study by Jang and Tsai [59] showed that a teacher's TPACK is directly related to the amount of their teaching experience. Teaching experience and gender were also confirmed to be the factors affecting the TPACK among Science teachers from secondary schools by the following study [60]. The ways teachers think of and use technology to improve teaching Science may be significantly affected also by the structure and content of a given subject [49].…”
Section: Theoretical Framework (Tpack)mentioning
confidence: 62%
“…Koehler ve Mishra'nın (2009) çalışmaları ile eğitim teknolojilerinin öğretim programları içerisinde entegre edilmesinin etkili öğrenme için önemli bir adım olduğu anlaşılmıştır. Bu durum öğretmenlerin farklı teknolojik araçları kullanmasını ve teknoloji okuryazarlıklarını geliştirmelerini bir zorunluluk haline getirmektedir (Jang ve Tsai, 2013). Bununla birlikte yapılan çalışmalarda öğretmenlerin teknolojiyi eğitim ortamlarında kullanmaya kendilerini hazır hissetmedikleri görülmektedir (Çelik, Şahin ve Aktürk, 2014).…”
Section: Literatür Taramasıunclassified
“…One particularly useful framework relevant for STEM workplace technology application is the Technological Pedagogical Content Knowledge (TPACK) framework (Koehler & Mishra, 2009;Koehler, Mishra, & Cain, 2013;Mishra & Koehler, 2006). TPACK considers how teachers use the unique affordances of technology to transform content and pedagogy for learners (Baran, Chuang, & Thompson, 2011;Jang & Tsai, 2013;Lin, Tsai, Chai, & Lee, 2013). The TPACK framework integrates the dimension of technological knowledge with Shulman's original construct of pedagogical content knowledge (PCK) (Shulman, 1987).…”
Section: Technological Pedagogical Content Knowledge (Tpack)mentioning
confidence: 99%